Optical Fiber Communication Conference (OFC) 2021 2021
DOI: 10.1364/ofc.2021.m3j.2
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of 470 GHz Bandwidth Wireless Transmitter Based on Photo-mixer for Simultaneous Transmission of Photonics-generated Signals in All-Band 6G Systems

Abstract: We experimentally demonstrate a 40-510 GHz all-band wireless transmitter covering the Q-, V-, W-, D- and THz-band communication links simultaneously. This is the first demonstration that a single photo-mixer is used to support simultaneous multiple transmissions over millimeter and terahertz channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
0
1
0
Order By: Relevance
“…They demonstrated experimentally that this new receiver could offer data rates of 115 Gbps at a frequency of 300 GHz over a link distance of 110 m. By using suitable dielectric lenses and digital signal processing algorithms, the authors in [122] demonstrated data rates of up to 124.8 and 44.8 Gbps for transmission distances of 54 and 104 m, respectively, for a 64QAM THz wireless system that does not use THz amplifier. In [123], the authors proposed and experimentally demonstrated a wireless transmitter that uses a single photo-mixer to support simultaneous multiple transmissions over millimeter and terahertz channels (i.e., 40 to 510 GHz).…”
Section: Advancement Of Experimental and Simulation Testbedsmentioning
confidence: 99%
“…They demonstrated experimentally that this new receiver could offer data rates of 115 Gbps at a frequency of 300 GHz over a link distance of 110 m. By using suitable dielectric lenses and digital signal processing algorithms, the authors in [122] demonstrated data rates of up to 124.8 and 44.8 Gbps for transmission distances of 54 and 104 m, respectively, for a 64QAM THz wireless system that does not use THz amplifier. In [123], the authors proposed and experimentally demonstrated a wireless transmitter that uses a single photo-mixer to support simultaneous multiple transmissions over millimeter and terahertz channels (i.e., 40 to 510 GHz).…”
Section: Advancement Of Experimental and Simulation Testbedsmentioning
confidence: 99%